Amelioracija T limfocitnih supstanaka, Inflammatorijskih faktora i gastrointestinalnih funkcija tradicionalnog menadžera rehabilitacije kineskih medicina u postoperativnoj kemoterapiji za rak Lung - Zou, Xiangni; Tang, Yuyang; Shi, Pei (Journal of Medical Biochemistry, 2025)
Background: To analyze the influence of Traditional Chinese Medicine (TCM)-characteristic rehabilitation management on T lymphocyte subsets, inflammatory response, and stress response during the postoperative chemotherapy of lung cancer (LC), aiming to provide a more reliable and valuable reference for future clinical treatment of LC. Methods: A total of 189 LC patients who were admitted to our hospital from July 2023 to June 2024 were enrolled in this research. Among them, 107 patients who did not receive TCM-characteristic rehabilitation management were regarded as the control group, while the other 82 patients who underwent such management were designated as the observation group. The levels of inflammatory factors and stress response markers before and after treatment in both groups were compared, includes hypersensitive-C reactive protein (hs-CRP), interleukin-6 (IL-6), superoxide dismutase (SOD), malondialdehyde (MDA), and glutathione peroxidase (GSH-Px). Additionally, the T lymphocyte subsets [CD3+, CD4+, CD8+, and natural killer (NK) cells] and gastrointestinal function were detected. Finally, we investigated the psychological status and sleep of the patients.Results: After the completion of treatment, it was observed that the levels of hs-CRP, MDA, and the proportion of CD8+ T lymphocyte subsets in the observation group were all significantly reduced compared with the control group (P